Polar Code application areas in the Arctic - Karahalil, Meric; Ozsoy, Burcu; Oktar, Ozgun (Springer Science and Business Media LLC, 2020)
The improvement of the International Code for Ships Operating in Polar Waters (Polar Code) has been a long process and is based on the previous International Maritime Organization (IMO) instruments. It aims at mitigating the risks of harsh environments and weather conditions for safe operations and the prevention and control of maritime pollution from ships in the polar regions. It is essential to understand the challenges pertaining to polar circumstances and reasons for maritime casualties in order to mitigate future risks. While maritime activities are increasing in the Arctic, little attention is being paid to some of the northernmost regions that are greatly influenced by the Arctic climate and are excluded from the Polar Code. The marine boundaries of the Arctic region have been defined differently by the Arctic Council Working Groups based on physical, geographical, and ecological characteristics. However, the boundaries of the Polar Code are not compatible with any of them. In this study, we analyze the extent of sea ice changes and the maritime traffic in the high north and also evaluate maritime safety in the frame of the application of the Polar Code boundaries in the Arctic.